To the Problems of Monitoring Research of Peculiarities Didactic Adaptation of Students of Higher Pedagogical Educational Istitutions at Education-Qualificational Level „ Junior Specialist ” - Halus, Olexander (Pedagogical Discourse, 2012)
Peculiarities of didactic adaptation of students of higher pedagogical educational institutions at education-qualificationallevel “Junior Specialist” on the basis of monitoring possibilities are studied in the article